Hamstring syndrome in collegiate track athlete - Daddario, S.; Burkey, T.; Wallace, J (Journal of Athletic Training, 2019)
Background: The patient was an 18-year-old female track and field sprinter with no significant medical history. She reported to the athletic training room complaining of posterior right thigh pain and had tenderness over the biceps femoris. Pertaining to ROM, her knee flexion had slight deficiency, her knee extension was WNL, she had discomfort with hip flexion, and hip external rotation was lacking when compared bilaterally. Following a thorough examination, the athletic trainer concluded that this athlete had a hamstring strain and would be withheld from participating in sport-related activity until symptoms subsided. Further, she would begin an exercise rehab program. The athlete's symptoms would diminish but would then show up in different spots along muscle with some numbness after rehabilitation sessions. Following 12 weeks of rehabilitation exercises, the symptoms subsided, and the athlete was allowed to return to sport. The following athletic season, the athlete reinjured her hamstring and clinical findings from the evaluation were similar to the initial injury. No new source of pain could be identified; however, she presented with one new symptom: a complaint of hamstring soreness/tightness when sitting. The athlete saw a physician in her hometown and the possibility of a hamstring syndrome diagnoses was presented. Differential Diagnosis: Hamstring strain or biceps femoris tendinopathy were considered. An MRI revealed no noticeable deformity. With the addition of soreness/tightness when sitting and no gross deformity noted, the potential diagnoses for hamstring syndrome was presented. Treatment: After visiting with the team doctor it was suggested to continue the exercise rehabilitation program and the official diagnoses of hamstring syndrome was documented. After the athletic trainer did some researching, it was stated in the literature that adding a vibration plate to the rehabilitation program could potentially relieve symptoms. Using a local chiropractors offi ce that had a vibration plate, the athlete was scheduled to work out on the vibration plate two for twelve minutes times per week, over three weeks. After four weeks the athlete had complete relief of symptoms that she had suffered from for over a year. The rehabilitation program was as follows; quarter squat, quarter squat hold with heel lift, full squat hold, RDL hold, seated hamstring stretch (thigh on plate) with the vibration plate set at 45-megahertz pulse. Then the athlete would perform single leg lunge hold, single leg lunge hold with toe up, single leg quarter squat hold, standing single leg hamstring stretch, seated hamstring stretch (on floor with heel on plate) with the vibration plate at a setting of 40-megahertz pulse. Each exercise was performed for 60 seconds with minimal rest in between sets. Uniqueness: This case is unique due to the conclusion of hamstring syndrome which is an uncommon diagnosis. However, it could be what is truly happening in athletes experiencing chronic, reoccurrent strains. If this is the case, then the athletes with a potential hamstring syndrome must be treated differently than an athlete with an acute hamstring strain. Using this research, it could offer an athletic trainer a method to solve an athlete with a chronic hamstring complaint. Conclusions: The potential for a diagnoses of hamstring syndrome presents a possible explanation to athletes that suffer from chronic or repetitive hamstring injuries. Due to the lack of research or information on hamstring syndrome, there is no true diagnostic criteria or rehabilitation programs for this syndrome. This case study could introduce athletic trainers to hamstring syndrome and provoke thought when working to rehabilitate an athlete suffering from chronic hamstring strains. In addition, using a vibration plate for hamstring injuries could be a benefi t to athletes with a hamstring injury.